PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, BUDAYA ORGANISASI, DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMA DI KECAMATAN PALMERAH - Mohammad Radjib; Yulita Pujilestari; Ruknan Ruknan (STKIP Pesisir Selatan, 2026)
This study aims to analyze the influence of Principal Leadership, Organizational Culture, and Work Motivation on Senior High School Teachers’ Performance in Palmerah District, West Jakarta. The study employed a quantitative approach using a survey method. The population consisted of all senior high school teachers in Palmerah District, with a sample of 126 teachers selected through proportional sampling techniques. Data were collected using a structured questionnaire based on a five-point Likert scale. The data were analyzed using descriptive and inferential statistical techniques, including classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results indicate that Principal Leadership, Organizational Culture, and Work Motivation each have a positive and significant effect on Teachers’ Performance. Simultaneously, the three independent variables significantly influence teachers’ performance, with an R Square value of 0.653, indicating that 65.3% of the variation in teachers’ performance can be explained by principal leadership, organizational culture, and work motivation, while the remaining percentage is influenced by other factors outside the research model. These findings suggest that improving teachers’ performance requires a comprehensive and integrated approach by strengthening principal leadership, fostering a supportive organizational culture, and enhancing teachers’ work motivation in a sustainable manner.